Undiagnosed Behçet's Disease Complicated by Multiple Pseudoaneurysms and COVID-19 Infection - Mehta, Aanchal; Shakarchi, Julien Al; Meecham, Lewis; Vijay, Santhosh; Downing, Richard (International Journal of Angiology, 2021)
Behcet's disease (BD) is a rare multiorgan systemic disorder characterized by recurrent episodes of acute inflammation. Involvement of the vascular system, gastrointestinal tract, and central nervous system portends a poor prognosis.We report the case of a 54-year-old man who presented with a 2-week history of symptoms attributable to infrarenal aortic and left tibioperoneal trunk pseudoaneurysms, defined by CT angiography which also revealed right lower lobe pulmonary artery (PA) and right anterior tibial arterial aneurysms. A prior history of recurrent oral ulceration, periodic fever, cerebral venous sinus thrombosis, and aseptic endocarditis with pulmonary emboli invoked a diagnosis of BD. Immunosuppression was commenced immediately, following synchronous endovascular and open arterial intervention, except the PA aneurysm.He developed a fever and cough 8 days postoperatively as a consequence of COVID-19 infection from which he recovered without complications.The management of the patient's four aneurysms in different vascular territories and postoperative COVID-19 infection in the presence of mandatory immunosuppression are discussed.
Keywords: COVID-19; Behcet's disease; pseudoaneurysm; SARS-CoV-2; immunosuppression; endovascular repair; anastomotic complication